3D printing as an effective tool for Transmit-array design at Ka band - Matos, S.; Costa, J. R.; Felício, J.; Fernandes, C. A. (Simposium Nacional de la URSI, 2022)
Transmit-arrays (TAs) can be a cost-effective solution for Satellite on-the-Move (SoTM) applications. Combining the flexibility of TAs with 3D printing can further enhance the lowcost potential of these antennas. This work shows that Fuse Deposition Modelling (FMD) 3D printing technique can be effective even for demanding designs, as the one considered in this study. A dielectric TA antenna with wide mechanical beam scanning (up 50 degrees) with an extremely low profile (F/D=0.34) and 26 dBi maximum gain at 30 GHz is optimized. Although the resulting aperture is thicker and have higher losses comparing with solutions based on printed circuit board (PCB) technology, we show that the performance of this low-cost antenna is still competitive. We study how different ways of crafting the TA phase correction in the dielectric block can improve the performance of the antenna.